Textiles and their use in microbial protection focus on COVID-19 and other viruses - Periyasamy, Aravin Prince; Venkataraman, Mohanapriya; Militky, Jiri (Material engineer) (Textile Institute professional publications, 2021)
"Textiles and Their Use in Microbial Protection: Focus on COVID-19 and Other Viruses provides readers with vital information about disinfection mechanisms used in textile applications in the fight against dangerous microbes and viruses. It is aimed at textile and materials engineers as well as readers in medical fields and offers a comprehensive view of fundamentals and solutions"--